2001
DOI: 10.1039/b108860b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tailored bimodal mesoporous materials with independent control of the dual pore size distribution

Abstract: A new synthesis method is presented to prepare multistructured porous materials through a fully chemical route that allows control of the smaller and larger mesopore sizes independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…The possibility of combining surfactants to produce bimodal pore size distributions with large pores providing access to smaller pore systems for high surface area and possibly molecular size recognition would find many applications. Recently, various types of hierarchically (macro-micro [23,24] macro-meso [3,17], meso-micro [25,26], and meso-meso [4,[27][28][29][30][31][32][33][34][35]) porous materials have been synthesized in an effort to prepare systems combining larger pores and smaller pores. In the case of Pluronic surfactant mixtures, early work results suggested that the resultant mesopore structures and pore sizes were a simple average of the individual surfactants [22,36].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of combining surfactants to produce bimodal pore size distributions with large pores providing access to smaller pore systems for high surface area and possibly molecular size recognition would find many applications. Recently, various types of hierarchically (macro-micro [23,24] macro-meso [3,17], meso-micro [25,26], and meso-meso [4,[27][28][29][30][31][32][33][34][35]) porous materials have been synthesized in an effort to prepare systems combining larger pores and smaller pores. In the case of Pluronic surfactant mixtures, early work results suggested that the resultant mesopore structures and pore sizes were a simple average of the individual surfactants [22,36].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the increasing capabilities to synthesize advanced materials with tailor-made pore networks, with selfassembly techniques, such as surfactant templating (Sun et al, 2001b), this article addresses the optimal structure of bimodal, multistructured porous catalysts, with a given constant nanoporosity (imposed by the use of a zeolite or other microporous material that the catalyst particles are prepared from), and a variable large-pore network which we aim to optimize. In this article, we depart from the established approach to the optimization of multistructured catalysts (for example, Keil 1999), where the main targets of the optimization are typically the micropore radius and porosity, whereas the structure of the large-scale pore network is considered of lesser interest.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in NZ the intra-crystalline diffusion barriers are supposed to be much less because of lower size of the crystal and hence it may be expected to show better activity for most of the typical reactions catalyzed by ZSM-5 such as light paraffin aromatization. This multiporous material can also prove to be of great interest in sorptive separation processes [18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%